Postgraduate Education in Psychiatric Nursing in Israel: Closing the Gap. (1st December 2014) - Haron, Yafa; Gun-Usishkin, Monica; Shor, Razia; Tran, Dror; Riba, Shoshana
<x xml:space="preserve">Abstract</x> Deinstitutionalization policies are being gradually implemented in Israel. Most recently, an insurance reform has been approved, in which mental health services will be included in the HMO's service package. As most Israeli mental health nurses are currently employed in institutional settings, the Ministry of Health's Nursing Division seeks to estimate their scope of employment in preparation for the anticipated changes. The aim of this study is to describe present-day professional practice characteristics of qualified psychiatric nurses and identify practice areas for which advanced training may be required. The research design is cross-sectional on a national level, including all state psychiatric hospitalization services. A countrywide sample of nurses with post-basic training in state psychiatric hospitals identified areas of practice in which further training may be required: psychotherapy intervention (60% of respondents); consultation for the elderly (60%); care prescriptions (64%); community drug treatment management (69%); and referral to professionals and community resources (56%). Nurses reported gaps in continued care and community rehabilitation activities. These findings have training implications in an era of increased focus on chronic mental illness in the community.